The Implementation of the Yanbu'a Method in Learning to Read the Quran at TPQ Al Mujahhadah Dusun Suka Damai, Tenggulun Village, Tenggulun District Aceh Tamiang Regency - Ahmad Hadadi; Zailani Zailani (UMSU, 2022)
This study aims to find out how to use the Yanbua'a method to improve the reading of Quran at TPQ Al Mujahhadah, Dusun Suka Damai, Tenggulun Village, Tenggulun District, Aceh Tamiang Regency. The primary purpose of this research is to find out how fluent students are in reading Quran after using the Yanbu'a method, the benefits obtained in using the Yanbu'a method in reading Quran, as well as how to implement the Yanbu'a method in the research's locations. The main point of this study is about how the quality of reading and the level of fluency mastered by students in reading the Al-Quran as a way of life for Muslims. Based on the research, it turns out that the Yanbu'a method has an excellent effect on improving the quality of reading and fluency in reading the Quran for students. Yanbu'a method teaches three things in each stage, such as emphasizing the justification of the articulation of the letters, memorising the verses being studied and being able to write them down, then with this series of processes students were required to be very consistent in improving fluency in reading Quran properly and correct.